(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the integration of Artificial Intelligence (AI) into systematic literature review (SLR) methodologies within literary studies. It focuses on combining AI tools with traditional methods to create a hybrid framework that supports interpretive depth and methodological rigor. Benefits, challenges, and implementation strategies are analyzed based on recent scholarly sources. By expanding on the theoretical foundation of SLR, examining case studies of AI integration, and considering ethical and pedagogical implications, this study provides a comprehensive roadmap for researchers and educators seeking to adapt to the digital transformation of research practices.